Evaluación estructural del edificio del colegio de ingenieros civiles del Guayas y su respuesta ante la norma vigente NEC 2015 - Subía Pérez, Karina Paola (2025)
This thesis evaluates the behavior and structural vulnerability of the building of the College of Civil Engineers of Guayas, located in the Tarqui Parish north of the City of Guayaquil, based on a comparative study under the regulations of the Ecuadorian construction code CEC 1977, in force at the year of construction of the building and the NEC 2015 in force to date. To do this, it begins with the collection of information about the structure (building plans: architectural and structural, year of construction), the seismic zoning of the soil is also taken as a reference, based on the NEC 2015, which grants a soil type D, in order to begin with the creation of the spectra, through the structural analysis using the ETABS program V.21.1.0, considering the structural plans of the building dating from 1986 and contrasting with the structural survey and experimental tests of 6 cores taken from beams and columns to verify the strength of concrete, carried out in February 2022..............